2014
DOI: 10.1103/physrevlett.112.184501
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-Driven Enhancement of Heavy Particle Clustering in Turbulent Flow

Abstract: Heavy particles suspended in a turbulent flow settle faster than in a still fluid. This effect stems from a preferential sampling of the regions where the fluid flows downward and is quantified here as a function of the level of turbulence, of particle inertia, and of the ratio between gravity and turbulent accelerations. By using analytical methods and detailed, state-of-the-art numerical simulations, settling is shown to induce an effective horizontal two-dimensional dynamics that increases clustering and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
159
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(187 citation statements)
references
References 14 publications
25
159
3
Order By: Relevance
“…The asymptotic independence of a fractal dimension on St was found in numerical simulations in [24] (see statement of independent work below), see also [34]. When gravity is strong, a new pattern of vertical clustering of sedimenting particles was recently observed [35].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The asymptotic independence of a fractal dimension on St was found in numerical simulations in [24] (see statement of independent work below), see also [34]. When gravity is strong, a new pattern of vertical clustering of sedimenting particles was recently observed [35].…”
mentioning
confidence: 90%
“…The latters' motion is influenced by gravity most significantly: the typical value of the ratio F r of acceleration of air parcels to g is small [3]. Indeed, recent simulations indicate that in this case gravity plays dominant role in the formation of particles' density [24]. Inclusion of gravity into the theory is thus necessary to describe rain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings were instrumental in highlighting the role of gravity on the clustering and the enhancement of settling velocities of heavy particles in a flow. More recently, inertial effects on settling particles were analysed using direct numerical simulations of fully developed homogeneous isotropic turbulence [17,18,[34][35][36]. These revealed that gravity can lead to major modifications of particle clustering, relative velocity and pair statistics, which could be characterized as a function of St and the ratio of turbulent to gravitational acceleration: a η /g.…”
mentioning
confidence: 99%
“…In presence of gravity (Wang & Maxey 1993) identified a preferential sweeping effect that increases the settling velocity. Recently, Dejoan & Monchaux (2013) and Bec, Homann & Ray (2014b) further discussed the influence of the Stokes number on the particle clustering in this situation.…”
Section: Introductionmentioning
confidence: 99%